The south is a battleground: Memories and continuities of sexual and gender dissident activisms in Andalusia - Mendoza Albalat, Diego (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This paper aims to recovery of the historical memory of sexual and gender dissidence activism in Andalusia. To this end, on the one hand, I have drawn up a historical account of these struggles since they began to take shape in the 1970s up to the present day. On the other hand, I have analysed some of the axes that have been shared in these activisms in the different historical periods. In order to address these objectives, I have implemented a qualitative methodology that combines various research techniques such as interviews, participant observation and the search for information in archives.